Assessment of Serum Vascular Endothelial Growth Factor Levels in Pregnancy-Induced Hypertension Patients - Vibha Tandon; Swati Hiwale; Dnyanesh Amle; Tripti Nagaria; Pradeep Kumar Patra (Journal of Pregnancy)
Objective. The objective of the study was to assess the serum vascular endothelial growth factor (VEGF) levels in peripheral blood of patients with pregnancy-induced hypertension (PIH) and find association between serum VEGF levels and PIH. Methods. Thirty-five PIH subjects, 35 normal pregnant females, and 20 normal healthy females were included in the study. Detailed history, clinical examination, and relevant biochemical parameters were assessed; serum VEGF levels were estimated using Double-antibody enzyme-linked immunosorbent assay. Results. The study groups were found to be age matched (p=0.38). VEGF level in the pregnancy-induced hypertensive group (median = 109.19 (3.38±619)) was significantly higher than the normal pregnant (median = 20.82 (1.7–619)) and control (median = 4.92 (1.13–13.07)) group and the difference between these three groups was significant (p<0.0001). The 3 groups are found to be significantly different in terms of RBS (p=0.01), urea (p<0.0001), creatinine (p=0.0005), AST (p=0.0032), ALT (p=0.0007), total protein (p=0.0004), albumin (p<0.0001), calcium (p=0.001), and sodium (p=0.02), while no statistically significant difference was found between total bilirubin (p=0.167), direct bilirubin (p=0.07), uric acid (p=0.16), and potassium (p=0.14). Conclusion. Significantly higher levels of serum VEGF were noted in PIH subjects compared to normal pregnant and control subjects.